The influence of the personal values of the workers in the performance of the work teams - محمد علي عالية جواد (Journal of Economics and Administrative Sciences, 2011)
The research aims to know the impact of workers values on their performance which is reflected on increasing productivity and improving its quality as well as the organization’s progress and success. Application of this research took place in the General Company Of Electrical Industries; it contained four main pillars; the first involved research methodology، regarding the problem، importance، aim، basic theory، and method of data collection، the second is dedicated to the theoretical framework related to the research basic variables (values and workgroups) the third is assigned to analyze the actual data by using number of statistical methods، such as mathematical medium and standard deviation and also spearman ranking to identify the degree of coloration between the research’s variables and the last is the simple linear regression to know the measure of impact workers’ values on their performance within the workgroups، then the fourth pillar dealt with several Conclusions and Recommendations، the most important is the company’s adoption to personal، organizational and religious criteria of individuals to promote workers’ performance and increasing their productivity; therefore this research focused on developing the team work spirit to achieve involvement and loyalty to organization، with a focus on forming working groups out of distinguished and qualified workers who have high personal values، to achieve both individual and organizational goals.